Analysis of Variation E7016 Electrode Heating Time and Humidity on E7016 Electrode Tensile Strength of Joints Welding Material SS400 - Junaidi, Ahmad; saputra, Dimas Ariya; Wilza, Romi; Hendradinata, Hendradinata (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2024)
This research aims to determine the effect of variations in heating time and humidity of the E7016 electrode on the tensile strength of welded joints in SS400 material. The research was carried out using three humidity levels and two electrode heating durations (2 hours and 3 hours) at a temperature of 260°C. The research results show that electrode humidity and heating time have a significant influence on the tensile strength of the welded joint. The highest tensile strength value was found in the welding variation using welding wire without treatment with heating for 3 hours with an average of 529.62 N/mm2, then the lowest tensile stress was found in the outdoor electrode humidity treatment variation with a heating time of 2 hours amounting to 378.12 N/mm2. The analysis was carried out using the two ways ANOVA method to analyze the resulting tensile strength data. The analysis results show that electrodes heated for 3 hours produce higher tensile strength compared to electrodes heated for 2 hours